Life-cycle cost analysis of infrastructure pavement applications in Western Australia - Whyte, Andrew; Gayner, L. (2013)
Life-cycle cost analysis (LCCA) is an engineering tool to assist design specification decisionmaking, estimate whole-life cost of civil engineering projects and help clarify sustainable choices. This paper investigates the use, process and applicability of LCCA techniques for construction inWestern Australia, and examines relevance with current case-study material. As recycled (waste-arising) construction materials are becoming an increasingly available market resource for new roads, it becomes important to address the (whole) economic impacts in long-term applications of the design specification alternatives that utilise recyclates. Recycled concrete, recycled demolition-arisings and recycled asphalt materials will be compared against their virgin material equivalents over realistic life-cycle periods of 30, 60 and 90 years to assess the extent to which environmental and economic considerations are aligned for WA pavements. Using an empirically calculated discount rate of 6.25% and testing over various life-spans it was found that sustainable (recycled) options are superior to (virgin) specifications when considering the range of alternative pavement specification design-options across the triple-bottom-line criteria of economic, environmental and social factors. The implications of the results of the work conducted stress the benefits and importance of LCCA usage in the construction industry in WA to guide both monetary benefit and environmental sustainability.